PENDEKATAN NORMATIF DALAM POLITIK HUKUM TERHADAP REGULASI OMNIBUS LAW UNTUK PEMBANGUNAN BERKELANJUTAN - Kalalo, Olly Frida Adolf Wilem (At-Tanwir Law Review, 2025)
This study examines the Omnibus Law from a legal-political perspective using a normative approach to assess its effectiveness in sustainable economic development. The regulation aims to streamline bureaucracy to boost investment but poses challenges in labor protection, environmental sustainability, and governance. This study employs a normative legal method with a statute approach. The findings indicate that while the Omnibus Law enhances legal certainty for investment, it requires further evaluation to ensure a balance between economic growth and social and environmental protection.